ANALISIS LAPORAN KEUANGAN PERUSAHAAN SUBSEKTOR COSMETICS AND HOUSEHOLD PERIODE 2014 – 2018 - Pipit Rosiana Damayanty; Endang Taufiqurahman (INVOICE : JURNAL ILMU AKUNTANSI, 2021)
This research was conducted with the aim of knowing how to calculate financial ratios, financial performance developments, and financial performance comparisons between Cosmetics and Household industrial companies listed on the Indonesia Stock Exchange from 2014 to 2018. The research method used is descriptive quantitative. Meanwhile, the data source used is secondary, namely financial reports from the IDX and the websites of each company. Of the population of 6 (six) companies listed as the cosmetics and household subsector on the IDX, researchers took four samples for research. The four companies are PT Akasha Wira International Tbk, PT Martina Berto Tbk, PT Mustika Ratu Tbk, PT Mandom Indonesia Tbk. The ratios used to analyze financial performance in this study are liquidity ratio, solvability ratio, activity ratio, profitability ratio. To measure performance comparisons between companies, the Mean, Median, Mode, and Maximum calculation techniques are used using SPSS version 24 software. The results reveal that 3 (five) out of 4 (six) cosmetics and household subsector companies listed on the IDX have good performance. worst in terms of liquidity, solvency, activity and profitability. The three companies are PT Akasha Wira International Tbk, PT Martina Berto Tbk, PT Mustika Ratu Tbk. Meanwhile, PT Mandom Indonesia Tbk was identified as having the best performance. Keywords: Financial reports; financial ratio; financial perfomance